PERKEMBANGAN BENTUK PERTUNJUKAN TARI TANDUAK DI SANGGAR KELAMBU SUTO KENAGARIAN MUARO KECAMATAN SIJUNJUNG KABUPATEN SIJUNJUNG - Fani Gustinanda; Darmawati Darmawati; Zora Iriani (FBS Universitas Negeri Padang, 2014)
Abstract The purpose of article was to describe the development of the form of Tanduak Dance show at Sanggar Kelambu Suto Kenagarian Muaro Kecamatan Sijunjung Kabupaten Sijunjung. This was a qualitative research which used descriptive analysis method. The data was collected through library study, observation, interview and documentation. The data obtained was analyzed by classifying the data based on the conceptual framework. The result of the research indicated that the development of the form of Tanduak Dance show was influenced by the society’s willingness to preserve the dance, so that Awang who was one of them develop the new form of the dance. The development could be seen from some elements including movements, dancer, floor design, music, properties, costume and the place of the show. Kata kunci: Perkembangan, Bentuk, pertunjukan, dari, tari, Tanduak